PERANAN PENYULUH PADA PEMELIHARAAN TERNAK BABI LOKAL DI DESA GUMBO KECAMATAN TIOMNERI KABUPATEN LANNY JAYA - Jigibalom, Turi; Malingkas, J A; Oley, F S; Lombogia, S O.B (Universitas Sam Ratulangi, 2019)
ROLE OF CATTLE PIGS COUNSELORS MAINTENANCE OF LOCAL DISTRICT IN THE VILLAGE GUMBO TIOMNERI LANNY JAYA REGENCY. The study aims to determine characteristics and breeders perception toward extension activities in the District Gumbo village Tiomneri Lanny Jaya Regency Research has implemented since December, 1th until January 31th 2018 using survey method. Twenty two of pig breeders in the village pig farmers Gumbo Tiomneri District of Lanny Jaya Regency was selected by census as sample of respondents. Data analysis using scale of likert Study results indicated that breeders perception of the role of agriculture extension agent as a motivator and facilitator in the District Gumbo village Tiomneri Lanny Jaya Regency was already optimal, or in other words the role of extension officers in performing their duties was already good. The process of adoption of technology by pig farmers in the village of the District Gumbo Tiomneri Lanny Jaya Regency was varied from respondents..The role agriculture counselor as a motivator has succeed to change the habits of farmers tradition that used to keep cattle in the house where they live (home honai) but by now farmers have made pig pen outside their house.Keywords: Role of Extension agent, pigs, Gumbo..